Diálogos de recriação entre literatura e cinema: As Eréndiras do verbo e da imagem em movimento - Pereira, Luis Eduardo Santos [UNESP] (My University, 2020)
The main object of study assumed in this paper are the media and semiotic dialogues of the relationship literature-cinema having cultural contexts as background. From multiple factors and study models which include cinema, the aim is to analyze the movement of the creative process between the works La increíble y triste historia de la candida Eréndira y su abuela desalmada (1972) by García Márquez and the film Eréndira (1983) by Ruy Guerra. In addition to looking after a relationship of analysis in which the film is only based on the story, it is sought to think how the cultural contexts of the artists and the potential representatives of the media resignify readings that are materialized by creating an interpenetration of the artistic discourses. Therefore, this paper strives to present cross-readings that make it possible to understand treatments of cultural issues in the story from the point of view of cinematographic resources and the same in reverse.
Dialogues of recreation between literature and cinema: The Eréndidas of the verb and the image in motion
Keywords: Cinema; Gabriel García Márquez; Intermidiality; Literature; Ruy Guerra